The relationship of nutritional status and dietary pattern with the incident of prediabetes at productive age in the Mangkubumi, Tasikmalaya city, Indonesia.: English - AISYAH, Iseu Siti; NENI, Neni; WARDANI, Yusrima Syamsina (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Prediabetes is the condition of a person whose blood sugar levels are more than normal but is not yet said to be suffering from diabetes mellitus. Prediabetes is a transitional stage that can be reversible leading to a normal condition if handled well or irreversible to diabetes if not handled properly. This research aims to determine the relationship between nutritional status and eating patterns (carbohydrates, fats, and so on) with the incidence of prediabetes in productive age. Method : This research uses a quantitative approach with an observational analytical study design, namely cross-sectional. The respondents of this research are of productive age in the Mangkubumi Community Health Center Work Area. The total number of samples studied was 125 people taken using the purposive sampling technique. Distribution of the number of samples in each sub-district with a high incidence of obesity in the Mangkubumi Health Center Working Area, namely Mangkubumi Sub-district with 58 people, Karikil Sub-district with 32 people, Cipari Sub-district with 35 people using proportionate random sampling. Results : Analysis was carried out on 125 research subjects with most were female (63.2%), employment status not working (49.6%), aged 19-59 years (88.8%), high school education (30.4%), over nutritional status ( 48 .8%), eating patterns with sufficient carbohydrate intake (63.2%), sufficient fat intake (60%), insufficient fiber intake (56.5%), and those with normal blood sugar levels (60%). There is a relationship between nutritional status and diet (carbohydrates, fat, and fiber) with the incidence of prediabetes in productive age in the Mangkubumi Community Health Center working area with a p-value of 0.000 for each. Conclusion : Based on the research results, it would be better to improve pre-diabetes screening and educate about healthy eating patterns in the productive age group at Posbindu to prevent the occurrence of type 2 diabetes mellitus.